Symbolic computation: systems and applications - Juozapavičius, Algimantas (Nonlinear Analysis: Modelling and Control, 1998)
The article presents an overview of symbolic computation systems, their classification-in-history, the most popular CAS, examples of systems and some of their applications. Symbolics versus numeric, enhancement in mathematics, computing nature of CAS, related projects, networks, references are discussed.
Keywords: none